2022
DOI: 10.1371/journal.pone.0266439
|View full text |Cite
|
Sign up to set email alerts
|

Underrepresentation of women in computer systems research

Abstract: The gender gap in computer science (CS) research is a well-studied problem, with an estimated ratio of 15%–30% women researchers. However, far less is known about gender representation in specific fields within CS. Here, we investigate the gender gap in one large field, computer systems. To this end, we collected data from 72 leading peer-reviewed CS conferences, totalling 6,949 accepted papers and 19,829 unique authors (2,946 women, 16,307 men, the rest unknown). We combined these data with external demograph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…By extracting the e-mail address associated with each author in our systems papers, we can roughly categorize author with a uniquely identifiable affiliation as either in government, academia, or industry. 2 Of the 13.9% authors with an industry affiliation, 8.8% were women, not much lower than the overall rate of women.…”
Section: Hypothesis 5: Fewer Women Pursue Research In Industrymentioning
confidence: 87%
See 1 more Smart Citation
“…By extracting the e-mail address associated with each author in our systems papers, we can roughly categorize author with a uniquely identifiable affiliation as either in government, academia, or industry. 2 Of the 13.9% authors with an industry affiliation, 8.8% were women, not much lower than the overall rate of women.…”
Section: Hypothesis 5: Fewer Women Pursue Research In Industrymentioning
confidence: 87%
“…21 In our dataset, the representation of women varies considerably by country. 2 Even among the top 20 countries (by number of authors), representation varies from 2% in Portugal and Japan to 14% in Sweden (11.4% in the United States, the largest country with 55% of systems authors). We don't have evidence for gender stereotypes or cultural differences that are specific to computer systems, but we could hypothesize that when it comes to systems, some of the preceding hypotheses have the potential to sharpen preexisting cultural biases toward CS and sciences in general, such as the effects on work-life balance.…”
Section: Hypothesis 10: Women's Participation Rate In a Field Varies ...mentioning
confidence: 99%
“…This number alone bases it in the high end of the reported 10-44% of computer science conferences in Cohoon et al (2011). In comparison to newer studies, average in computer systems was reported to be only around 10% in Frachtenberg and Kaner (2022) and 30-70% in database research reported in late 2021 (Bonifati et al, 2022). The distribution of the number of the PerCom articles over the years is illustrated in Figure 1.…”
Section: Gender In Accepted Articlesmentioning
confidence: 88%
“…Various activities have taken place, over the specialized networks such as N2Women and inside the conference committees themselves, especially rising awareness of the female representation in different panels, committees, and reviewer boards, as well as keynote speakers (Martin, 2014). Focusing on the systems research in computer science, Frachtenberg and Kaner (2022) studied the conference factors and their influence on gender diversity: size of the conference, whether the double-blinded review was applied, diversity in conference organizational roles, and different diversity initiatives. However, they concluded none of these factors influenced significantly the gender ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation